Treatment of dural arteriovenous malformations involving the superior sagittal sinus. - Halbach, V V; Higashida, R T; Hieshima, G B; Rosenblum, M; Cahan, L (American Journal of Neuroradiology, 1988)
We report the diagnosis and treatment of seven dural arteriovenous malformations involving the superior sagittal sinus. The most common presenting symptom was headache, although two patients presented with hemorrhage. Embolization alone effected a complete cure in four patients, while a combination of embolization and surgery was used in the remaining three patients. The first of these had intraoperative exposure and embolization of multiple feeding branches of both middle meningeal arteries, which resulted in a complete cure without deficits. The second patient had multiple embolizations and surgeries with eventual resection of the involved sagittal sinus to effect a complete cure, which was complicated postoperatively by paraparesis. The third patient had preoperative embolization and subsequent surgical resection of the superior sagittal sinus, resulting in a complete cure without deficits. Because of their unique midline location, multiplicity of arterial feeders, and critical venous drainage, dural malformations involving the superior sagittal sinus often require unusual and aggressive forms of therapy.